Examining the Impact of Powtoon-Assisted Problem-Based Learning on Motivation and Critical Thinking in Primary Education - Yanuarto, Wanda Nugroho; Safitri, Eni (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to investigate the effectiveness of integrating Problem-Based Learning (PBL) supported by Powtoon in enhancing students’ motivation and improving their critical thinking skills in mathematics learning. The study responds to the growing demand for 21st-century competencies and the need for instructional approaches that foster active engagement and higher-order thinking. Method: This research employed a quasi-experimental design using a pretest-posttest control group approach. The participants consisted of fourth-grade primary school students who were divided into experimental and control groups. Data were collected through a learning motivation questionnaire and a critical thinking test, and subsequently analyzed using descriptive and inferential statistical techniques. Findings: The findings revealed that students in the experimental group demonstrated significantly higher levels of motivation and stronger critical thinking skills than those in the control group. The implementation of Powtoon-assisted PBL was associated with greater student engagement, improved understanding of mathematical concepts, and more active participation in problem-solving activities. Significance: This study highlights the potential of combining innovative pedagogical approaches with digital media to support meaningful mathematics learning. The integration of PBL and Powtoon contributes to the enhancement of both affective and cognitive learning outcomes. It provides empirical evidence for the development of instructional practices that promote essential competencies required in contemporary education.